Endothelial Dysfunction and Racial Disparities in Mortality and Adverse Cardiovascular Disease Outcomes. Issue 6 (30th March 2016) - Erqou, Sebhat; Kip, Kevin E.; Mulukutla, Suresh R.; Aiyer, Aryan N.; Reis, Steven E.
Abstract: Background: The contribution of arterial endothelial dysfunction (ED) to increased cardiovascular disease (CVD) risk among Blacks is not known. Hypothesis: We investigated whether peripheral arterial ED explains racial disparity in CVD events. Methods: Data from the Heart Strategies Concentrating on Risk Evaluation (Heart SCORE) study was used. Endothelial dysfunction was assessed by the Framingham reactive hyperemia index (fRHI), measured using pulse amplitude tonometry (PAT). Lower values of fRHI indicate more severe ED. The primary outcome of interest was combined CVD events and all‐cause mortality. Results: 1454 individuals (62% female, 40% Black, mean age 59 ± 8 years) had available data on fRHI (mean [SD]: 0.74 [0.46]). Over a mean follow‐up period of 8.0 ± 2.4 years (11, 186 person‐years), 116 events were observed. Black race, male sex, smoking, diabetes, blood pressure, triglycerides, C‐reactive protein, and interleukin‐6 were inversely correlated with fRHI in univariate models. In an unadjusted Cox regression model, fRHI was associated with 20% lower risk of the primary outcome events (hazard ratio [HR] per 1‐SD higher fRHI: 0.80, 95% confidence interval [CI]: 0.66‐0.97). However, this association was no longer significant after adjustment for CVD risk factors (HR: 0.90, 95% CI: 0.74‐1.11). In an age‐ and sex‐adjusted model, Blacks had 1.68 (95% CI: 1.16‐2.43) higher risk of primary outcome compared with Whites. This association was not significantly attenuated by addition of fRHI to the multivariable models. Conclusion: Black race is associated with increased risk of CVD events and mortality independent of its associations with ED, as measured by PAT.